Tactile self monitoring of attention to decrease off-task behavior of adolescents with intellectual disabilities and autism - Root, Jenny (East Carolina University, 2012)
The purpose of this study was to investigate the effects of tactile self monitoring of attention on off task behavior by students with Intellectual Disabilities and Autism in the self contained setting during independent tasks. Adolescents with Intellectual Disabilities and Autism demonstrate significant deficits in self management as demonstrated by off task behavior. The participants of the study were three public middle school students ages 12-13 with Intellectual Disabilities and Autism who receive all academic instruction in a special education classroom. The participants all displayed significant amounts of off-task behavior during baseline, including getting out of their seats, talking with or interrupting others, looking around the classroom at items not related to the task, not working on assigned tasks, engaging in bodily movements unrelated to or interfering with the assigned task or using materials for purposes other than completing the assigned task. A tactile self monitoring intervention was implemented using a multiple baseline design across three tasks. The independent tasks included reading, math, and vocational activities. The tactile self monitoring of attention was successful in decreasing the amount of time spent off task during independent work activities.
Tactile self monitoring of attention to decrease off task behavior of adolescent students with intellectual disabilities and autism
Keywords: Special education; Behavioral sciences; Education; Adolescents; Autism; Intellectual disabilities; Off task behavior; Self-management; Self-monitoring; Students with disabilities; Attention in adolescence; Youth with mental disabilities--Behavior modification; Youth with autism spectrum disorders--Behavior modification